Increasing the rating performance of paraffin up to 5000 cycles for active latent heat storage by adding high-density polyethylene to form shape-stabilized phase change material. (February 2022) - Rahmalina, Dwi; Rahman, Reza Abdu; Ismail
Highlights: SSPCM has a higher charging rate after 5000 cycles compared to pure paraffin. The rating performance of SSPCM is 30% faster than pure paraffin after 5000 cycles. Adding HDPE maintains the phase transition of paraffin at elevated cycles. Abstract: The unstable phase transition of pure paraffin limits its application, particularly for active latent heat storage (ALHS). In passive latent heat storage, the addition of high-density polyethylene (HDPE) can decrease paraffin's leakage rate, which is associated with unstable phase transition and increase its durability after a large thermal number. This study aims to discover the possibility to use HDPE as a shape-stabilizer to increase the paraffin's performance for the ALHS system. Pure paraffin and composite paraffin/HDPE (80:20 wt%) are prepared as the reference material. The evaluation is focused on thermal properties, stability and performance during charging and discharging under different thermal cycles. Thermal cycle treatment uses temperature as a working boundary where the sample is heated from 30°C to 150°C, then cooled back to 30°C and repeated until 5000 cycles. Three different cycle references are chosen (1, 1000 and 5000 cycles) for each evaluation. The melting temperature of paraffin is decreased from 61.6°C to 59.8°C after 5000 cycles where Paraffin/HDPE slightly decreased from 60.4°C to 60.1°C. The heat fusion is decreased by 8.7% and 2.9% for paraffin and Paraffin/HDPE, respectively. The isothermal phase change is observed for paraffin/HDPE even after 5000 cycles with a higher rating performance by 30% faster to complete one cycle than pure paraffin. The other thermal performance is discussed in detail within the article, including the phase transition model during charging and discharging for the sample.